THERAPEUTIC COMMUNICATION IN “DREAM” SONG LYRICS CREATED BY PUTRI ARIANI - Muhamad Faizal Nailusidqi; Fery Wijayanto (Faculty of Letters Universitas Balikpapan, 2024)
This article aims to analyze therapeutic communication in the lyrics of the song “Dream” by Putri Ariani. This research methodology uses a qualitative approach with Van Dijk's discourse analysis method. The results showed that the lyrics of the song “Dream” have macro and micro structures that interpret the hope to be achieved as the main theme, and the superstructure consists of verse 1, verse 2, reff 1, verse 3, reff 2, reff 1, reff 2, coda. The lyrics of the song “Dream” by Putri Ariani provide therapy to listeners because it contains a message about the journey to achieve dreams will face difficulties that need to be faced by surrendering to God and always being grateful will lead to happiness. At the end of the song, the lyrics emphasize the belief to the listener about the existence of happiness as a therapeutic form of anxiety on the journey of life.